A population-based comparison of European and North American sinonasal cancer survival. Issue 4 (August 2018) - Unsal, Aykut A.; Kılıç, Suat; Dubal, Pariket M.; Baredes, Soly; Eloy, Jean Anderson
Abstract: Objective: Sinonasal cancers (SNC) are rare, thus limiting previous prognostic studies on a multinational level. The aim of this study is to utilize two population-based datasets to compare prognoses for SNC between the United States (US) and Europe. Methods: The European Cancer Registry (EUROCARE) database and the United States National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database were searched to identify survival of patients diagnosed with SNC between 1990 and 2007. Relative survival (RS) data were stratified by age group, gender, geographic location, and diagnostic time period. Results: 12, 541 SNC cases were identified in EUROCARE, while SEER identified 4, 312. Males comprised the majority in Europe (62.3%) and the US (58.3%). Most patients were over 55 years in Europe (77.0%) and the US (69.5%). Age over 75 was a statistically significant poor prognostic indicator for 5-year RS in the US (48.2%; 95% CI = [43.9, 52.4]) and Europe (38.5%; [34.7, 42.7]). Female gender imparted a favorable 5-year RS in all regions except in Central Europe. By region, the US had the highest 5-year RS (58.8%; [56.4, 61.1]) and Eastern Europe had the lowest 5-year RS (37.1%; [34.0, 40.6]). The aggregate European 5-year RS was 48.1% [46.4, 49.8]. Conclusion: SNC in Europe and the US most commonly affects males and individuals over the age of 55 years. Male gender and age over 75 are poor prognostic factors at 5 years. Five-year RS in the US is higher than the 5-year European aggregate RS.